DEFINING MEDICAL DEVICES: A COMPREHENSIVE OVERVIEW - Otabek Shavkatov; Yodgorbek Ismoiljonov; Zafar Juraev (Journal Park Publishing, 2024)
Medical devices play a pivotal role in modern healthcare, encompassing a wide range of instruments, apparatuses, implants, and software utilized in the diagnosis, treatment, monitoring, and prevention of diseases and medical conditions. This paper provides a comprehensive exploration of the definition of medical devices, considering various regulatory frameworks, classifications, and technological advancements shaping the field. By elucidating the multifaceted nature of medical devices, this paper aims to enhance understanding and foster discussion on the evolving landscape of healthcare technology.
Keywords: medical devices, global medical device, instrument, apparatus, medical equipment, contrivance, implant.